Ya manga sulat ni Pablo adti manga mangintu-uway dun ni syudad na Tessalonika 1st and 2nd Thessalonians with study guide. (Overseas Missionary Fellowship, 2008)
"Paul's letters to the believers in the city of Thessalonica"--Provided by publisher.